Validation and Implementation of an Ordering Alert to Improve the Efficiency of Monoclonal Gammopathy Evaluation. Issue 3 (28th November 2019) - Uljon, Sacha N; Simmons, Daimon P; Rudolf, Joseph W; Baron, Jason M; Dutta, Sayon; McEvoy, Dustin S; Murali, Mandakolathur; Dighe, Anand S
Abstract: Objectives: To evaluate the use of a provider ordering alert to improve laboratory efficiency and reduce costs. Methods: We conducted a retrospective study to assess the use of an institutional reflex panel for monoclonal gammopathy evaluation. We then created a clinical decision support (CDS) alert to educate and encourage providers to change their less-efficient orders to the reflex panel. Results: Our retrospective analysis demonstrated that an institutional reflex panel could be safely substituted for a less-efficient and higher-cost panel. The implemented CDS alert resulted in 79% of providers changing their high-cost order panel to an order panel based on the reflex algorithm. Conclusions: The validated decision support alert demonstrated high levels of provider acceptance and directly led to operational and cost savings within the laboratory. Furthermore, these studies highlight the value of laboratory involvement with CDS efforts to provide agile and targeted provider ordering assistance.